ADAPTING LANGUAGE INSTRUCTION FOR DIFFERENT ACADEMIC FIELDS (Web of Teachers: Inderscience Research, 2024)
The significance of tailoring language teaching to the particular requirements of various academic disciplines is examined in this article. It emphasises how every field, including the social sciences, sciences has unique linguistic needs, including conversation patterns, terminology, and conventions. The utilisation of real resources, an integrated skills approach, collaborative curriculum design, and specialised assessment methods are some of the tactics for customised instruction that are suggested in the article. Lastly, the topic of how technology might improve language learning through virtual collaboration and interactive tools is covered. All things considered, the paper emphasises how crucial individualised language training is to promoting academic achievement and successful communication in a multicultural and globalised society.